Fused Main Subjects - Neelameghan, A.; Gopinath, M. A. (Journal of Information and Knowledge, 1972)
The helpfulness of dividing the universe of subjects, in the first instance, into a few chunks called Main Subjects, is indicated. The need for a further division of some of the Main Subjects, is also mentioned. The principles used by Colon Classification in. arranging the Main Subjects in a helpful sequence, are referred to. The concept of Fused Main Subject and its formation are discussed with illustrative examples. Guiding principles for deeming a new Fused Main Subject as an adjunct of one or the other of the fusing Main Subjects are formulated. The use of Canon of Systematic Mnemonics for arranging two or more fused Main Subjects forming adjunct Main Subjects is illustrated. The application of these principles for determining the position of new Fused Main Subjects is illustrated. A census of some of the fused Main Subjects together with their class number in CC ed 7, UDC, and DC ed 18 is given. The resolution of a homonym by the concept of Fused Main Subject, with respect to CC numbers, is pointed out. The need for guiding principles for the arrangement of adjunct Main Subjects to a particular Main Subjects in helpful sequence is indicated.